Defining the sensitivity of cosmic ray muons to groundwater storage changes - Tramontini, Matías; Rosas-Carbajal, Marina; Zyserman, Fabio Iván; Longuevergne, Laurent; Nussbaum, Christophe; Marteau, Jacques (Comptes Rendus. Géoscience, 2024)
Quantifying groundwater storage variations is key for sustainable water resource management, estimating droughts and climate change impacts, and the environmental protection of the Critical Zone. Despite the many geophysical methods traditionally used to indirectly infer groundwater storage, there is still a gap in the spatial and temporal scales covered. Furthermore, the groundwater mass quantification is usually done through proxies as few methods characterize a physical property directly linked to the volumetric water content. In this work we employ for the first time, the muography method to investigate groundwater variations at the scale of 100 m. We study a mountainous karstic aquifer in the Mont Terri Underground Rock Laboratory (URL), Switzerland. We use a muon detector to compute a muon image of average density, and to study muon rate variations over time. After correcting these variations for atmospheric effects, we interpret the muon time series in terms of groundwater storage changes. Comparisons with river stream flow, and volumetric soil water content data, show similar variation patterns to the groundwater estimates from our muon measurements. Since we only observe significant changes in a particular region of the whole volume scanned by our detector, we analyze in detail the role of the geometrical setup in the sensitivity of muography to groundwater variations. We find that the geometrical relationship between the trajectories of detected muons and the topography has a significant effect in the amplitude of the detected variations. This finding points to a potential muon-based groundwater storage monitoring with optimized experimental setups to amplify the groundwater storage signal.